Readiness of Middle School Science Teachers in Implementing Kurikulum Merdeka: A Case of Public School in Sidoarjo - Ruchmana, Nadia Indra; Sartika, Septi Budi (Jurnal Pendidikan MIPA, 2023)
Abstract: This study aims to analyze the readiness junior high school science teachers in planning, implementing, and assessing science learning for science subjects according to the Kurikulum Merdeka Belajar. Research uses a qualitative method case study. Data collection used questionnaires, documentation and interviews. Research subjects were six science teachers. Data analysis refer Miles & Hubberman, namely; data collection, data condensation, data presentation (display), and data verification or conclusion drawing. Results showed everything was well prepared and in accordance with the Kurikulum Merdeka guidelines. The learning planning stage, science teachers review CP, make ATP and TP, make Teaching Modules, and compile assessments. The stage of implementing science learning according this Kurikulum Merdeka, it has an impact on students, where students are encouraged to be able contribute actively in the learning process. Addition, assessment stage, science learning is also in accordance with the Kurikulum Merdeka, namely by using congnitive and non-cognitive diagnostic assessments        Keywords: Kurikulum Merdeka, middle school, teacher readiness, science learning. Abstrak: Penelitian ini bertujuan untuk menganalisis kesiapan guru IPA SMP dalam perencanaan, pelaksanaan, dan asesmen pembelajaran IPA untuk mata pelajaran IPA sesuai dengan Kurikulum Merdeka Belajar. Penelitian menggunakan metode kualitatif studi kasus. Pengumpulan data menggunakan kuesioner, dokumentasi, dan wawancara. Subjek penelitian adalah enam orang guru IPA. Analisis data mengacu pada Miles & Hubberman, yaitu; pengumpulan data, kondensasi data, penyajian data (display), dan verifikasi data atau penarikan kesimpulan. Hasil penelitian menunjukkan semuanya telah dipersiapkan dengan baik dan sesuai dengan pedoman Kurikulum Merdeka Belajar. Tahap perencanaan pembelajaran, guru IPA mengkaji CP, membuat ATP dan TP, membuat Modul Ajar, dan menyusun penilaian. Tahap pelaksanaan pembelajaran IPA sesuai Kurikulum Merdeka Belajar dan memberikan dampak pada siswa, dimana siswa didorong untuk dapat berkontribusi aktif dalam proses pembelajaran. Selain itu, tahap penilaian, pembelajaran IPA juga sesuai dengan kurikulum mandiri, yaitu dengan menggunakan penilaian diagnostik kongnitif dan non-kognitif.    Kata kunci: Kurikulum Merdeka, sekolah menengah pertama, kesiapan guru, pembelajaran IPA.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp528-544